2003
DOI: 10.1128/jvi.77.13.7623-7634.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 2 Reverse Transcriptase Activity in Model Systems That Mimic Steps in Reverse Transcription

Abstract: Human immunodeficiency virus type 2 (HIV-2) infection is a serious problem in West Africa and Asia.However, there have been relatively few studies of HIV-2 reverse transcriptase (RT), a potential target for antiviral therapy. Detailed knowledge of HIV-2 RT activities is critical for development of specific highthroughput screening assays of potential inhibitors. Here, we have conducted a systematic evaluation of HIV-2 RT function, using assays that model specific steps in reverse transcription. Parallel studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 72 publications
4
13
0
Order By: Relevance
“…RT from 98CN009 was the least efficient enzyme in the panel for all three activities. Consistent with previous reports (14,27,49,56), the DNA polymerase and RNase H activities of RT from the HIV-2 strain EHO-287 were significantly less than those of most of the HIV-1 RTs.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…RT from 98CN009 was the least efficient enzyme in the panel for all three activities. Consistent with previous reports (14,27,49,56), the DNA polymerase and RNase H activities of RT from the HIV-2 strain EHO-287 were significantly less than those of most of the HIV-1 RTs.…”
Section: Methodssupporting
confidence: 80%
“…Six of the clones in the panel (94CY017.41, 92UG021, RU570, US, TAN1B, and EHO-287) represent the first cloning, expression, and purification of active RT enzymes from viral isolates of the corresponding clades. Where enzymatic activities of these isolates or close relatives have been reported separately (functional comparisons involving RTs [14,27,49,55]), our results are consistent with previous observations. Although one or two individual clones from within a given clade cannot represent the full range of enzymatic activities or drug sensitivities across the entire clade, the recombinant RT panel described here provides a useful cross section of natural lentiviral genetic diversity.…”
Section: Figsupporting
confidence: 83%
See 1 more Smart Citation
“…In another case, F214L occurred at least 2 months after the Q151M mutation. At position 227 in the primer grip region [Post et al, 2003], a tyrosine was observed in 91% of sequences from HIV-2-treated patients and in 50% of sequences from untreated patients (P < 0.05). Note, however, that amino acid substitution F227Y was selected in only one patient during the longitudinal analysis.…”
Section: Identification Of Suspected Nrti-resistance Mutationsmentioning
confidence: 98%
“…The frequency of RT switching from one RNA template to the other RNA depends on the balance between polymerase and RNase H activities, as proposed by the dynamic copy choice model (34). The RNase H activity of HIV-2 was also shown to be much lower than that of HIV-1 in vitro (56), although a more recent study indicated that they are comparable (48). If HIV-1 and HIV-2 differ in the balance of polymerase and RNase H activities in RT, then the RT molecules of these two viruses may switch templates at different frequencies and alter the observed recombination rates.…”
mentioning
confidence: 95%